"It takes a village": the sources and types of support in development of male cricket players. Issue 2 (February 2021) - Warmenhoven, John; Weissensteiner, Juanita R.; MacMahon, Clare
Graphical abstract: Abstract: Objectives: To explore the different types of support (e.g., financial, informational) and support providers (e.g., fathers, siblings) in the development of male cricket players across different levels of skill expertise. Methods: A quantitative questionnaire (developed as a part of a broader Australian Research Council Linkage project) assessing support providers and types of support accessed by players was distributed to participants through involvement with a national sporting organisation. Descriptive trends across support types for each provider were explored for the total cohort of athletes, n  = 1383 (as relative percentages), and community and elite differences were explored using chi-squared analyses ( p  < 0.05). Results: Mothers and fathers were primary providers of financial and emotional support (>80%), mentors offered meaningful sport-specific informational and technical (or coaching related) support, and siblings and peers played an integral development role in acting as fellow participants for practice and play. Access to coaching emerged as a dominant point of difference between community and elite players consistently across all support providers ( p  < 0.05). Mentors and siblings also featured more frequently for elite players across broader ranges of support factors ( p  < 0.05). Conclusion: Regardless of level of skill expertise, there were unique context-specific roles that different providers played in supporting cricket players. When differentiating between levels of expertise, elite players drew on more "contact" points to assist them in accessing the right type of coaching. Mentors and siblings also featured more frequently for elite players across a broader range of support factors. Taken together, these findings show that elite players are distinguished in their reliance on multiple components within a complex family system, bolstered by additional significant others. This work further underscores the previously limited exploration of social networks in athlete development, highlighting avenues for continued enquiry and action in sport development systems.